Sosialisasi Produk Pupuk Organik Cair dari Limbah Kulit Nanas dan Limbah Kulit Pisang dari Hasil Fermentasi spora Tricoderma sp dengan Bioaktivator Air Kelapa Kepada Masyarakat - Siti Chodijah; Sofiah Sofiah; Robert Junaidi; Meilianti Meilianti (CV. Era Digital Nusantara, 2026)
Implementation of community service activities in the form of technology transfer for the production of liquid organic fertilizer is an effort to utilize environmental potential in the form of household organic waste. This activity was carried out at RT 08 Demang Lebar Daun, Ilir Barat I. The method used in this activity is providing materials and demonstrations. The implementing team provided information on various organic waste at RT 08 Demang Lebar Daun, Ilir Barat I environment so that it could be used as a source of raw material for liquid fertilizer production. The demonstration experiment was led directly by the service team, including practical training in making liquid organic fertilizer from household waste materials, namely pineapple peels and banana peels at RT 08 Demang Lebar Daun. The transfer of liquid organic fertilizer production technology brings significant benefits, namely, increasing public knowledge about the use of residual organic waste as raw material for liquid fertilizer production, strengthening environmental health awareness, and economic added value will also increase. Furthermore, it allows farmers to reduce the cost of purchasing fertilizer and increase household income through the sale of liquid organic fertilizer.